Sustained gastrointestinal activity of dendronized polymer-enzyme conjugates - Fuhrmann, Gregor; Grotzky, Andrea; Lukic, Ruzica; Matoori, Simon; Luciani, Paola; Yu, Hao; Zhang, Baozhong; Walde, Peter; Schlueter, A. Dieter; Gauthier, Marc A.; Leroux, Jean-Christophe (Nature Chemistry, 2013)
Methods to stabilize and retain enzyme activity in the gastrointestinal tract are investigated rarely because of the difficulty of protecting proteins from an environment that has evolved to promote their digestion. Preventing the degradation of enzymes under these conditions, however, is critical for the development of new protein-based oral therapies. Here we show that covalent conjugation to polymers can stabilize orally administered therapeutic enzymes at different locations in the gastrointestinal tract. Architecturally and functionally diverse polymers are used to protect enzymes sterically from inactivation and to promote interactions with mucin on the stomach wall. Using this approach the in vivo activity of enzymes can be sustained for several hours in the stomach and/or in the small intestine. These findings provide new insight and a firm basis for the development of new therapeutic and imaging strategies based on orally administered proteins using a simple and accessible technology. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2021-06-29